Study on the relationship between the particle size distribution characteristics of ground granulated blast furnace slag and its mortar properties - He, Tusheng; Xu, Zengwei; Li, Zaibo; Zhao, Xuguang; Zhao, Sanyin; Liu, Yang (Frontiers in Materials, 2022)
This study adopted the Rosin-Rammler-Bennett (RRB) equation to model the particle size distribution (PSD) of ground granulated blast furnace slag (GGBFS) and prepared four groups of GGBFS powders with a characteristic particle size De=8–20 μm and uniformity coefficient n=0.9–1.4 by means of grading and combining blast furnace slag. In cases both with and without polycarboxylate superplasticizers (PCE), the fluidity and strength of the mortar were measured. The study found that without PCE, the aggregation of GGBFS had a significant negative impact on the mortar fluidity and hardened paste strength. With the addition of PCE, the properties of the mortar mainly depended on two factors, the specific surface area of the GGBFS and the differences in De and n between the GGBFS and Portland cement. At a given specific surface area of GGBFS, high hardened paste strength can be obtained through simultaneously lowering the De and increasing the n.